2021
DOI: 10.54029/2021fjn
|View full text |Cite
|
Sign up to set email alerts
|

Can immature granulocytes indicate mortality in patients with acute ischemic stroke?

Abstract: Background & Objective: Stroke is the most common cause of permanent disability and the most important cause of mortality. Acute ischemic stroke (AIS) reveals inflammation in the ischemic brain tissue. Ischemic tissue causes proinflammatory cytokine release and aggregation of immune cells. Therefore in this study, we aimed to investigate the role of immature granulocyte (IG) in showing 30-day mortality in patients with AİS. Methods: This study was designed as a single-centered, retrospective cohort study. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…7 Moreover, Korkut et al found that high IG levels were significantly associated with 30-day mortality in AIS. 5 Our study showed a statistically significant correlation between high IG value and short-term mortality in cases with AIS. In univariate and multivariate Cox regression analyses, IG% was an independent predictor of short-term mortality.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…7 Moreover, Korkut et al found that high IG levels were significantly associated with 30-day mortality in AIS. 5 Our study showed a statistically significant correlation between high IG value and short-term mortality in cases with AIS. In univariate and multivariate Cox regression analyses, IG% was an independent predictor of short-term mortality.…”
Section: Discussionsupporting
confidence: 55%
“…4 Whereas, only one study observes the relationship between IG and the 30-day mortality of AIS patients. 5 However, we could not find an article in the literature investigating the connection between immature granulocyte and long-time period mortality in patients with AIS. Therefore, we aimed to investigate the function of IG and other labels in predicting short-and long-time mortality in patients with AIS.…”
Section: Introductionmentioning
confidence: 87%
“…In their study, Korkut et al showed that the IG count effectively shows 30-day mortality in ischemic stroke patients. 22 Bedel et al found that the IG count was significantly associated with poor prognosis in spontaneous intracerebral hemorrhage. 23 In addition, in a recent study, it was shown that the IG count is effective in predicting hospital mortality in spontaneous intracerebral hemorrhage.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been discovered that the number and percentage of IG in peripheral blood help to predict complications and mortality in many diseases, such as sepsis, septic shock, local infection, coronary artery disease, acute appendicitis, and pancreatitis (3,4). Moreover, in one study, IG was associated with 30-day mortality in acute ischemic stroke (5). However, there is only one study on IG in the literature to predict mortality in patients with SICH, and the relationship between 30-day mortality and IG has been investigated (6).…”
Section: Introductionmentioning
confidence: 99%